Determinação de hidrocarbonetos policíclicos aromáticos, níquel e vanádio em frações ácidas, básicas e neutras de asfaltos virgens e envelhecidos - Claussen, Luís Evandro (2017)
Asphalt cement (AC) is a dark-colored binder material, consisting of a mixture of naturally occurring petroleum hydrocarbons or obtained from distillation, which contains small fractions of sulfur, nitrogen, oxygen and metals (Ni, V, Fe) . During the application of AC, the generated emission of the hot mix contains a large number of compounds, some of which being potentially harmful to the health of the professionals involved in these procedures. In addition, the occurrence of trace metals is of great analytical interest as they are corrosive and cause environmental pollution. With the aging process, there are changes in the chemical composition of the AC involving these compounds, resulting from reactions such as oxidation, condensation and dealkylation that lead to changes in the rheological properties of the matrix. In this work, the behavior of AC were studied for PAHs and derivatives (N-PACs and O-PAHs) and metals such as Ni and V against the modifications caused by aging (RTFOT/SUNTEST). First, the samples (virgin and aged) were separated into acidic, basic and neutral fractions of maltenes and asphaltenes. Next, a sample cleaning method was developed for analysis of PAHs and derivatives by LC-ESI-MS/MS. For the Ni and V studies, the total amount of these compounds was investigated by GFAAS and the loss of Ni and V metaloporphyrins (volatile compounds) of the AC using the DEC (extraction and collection device) was shown. The results showed that PAHs are more concentrated in the maltenic fraction and N-PACs and O-PAHs in the asphaltene fraction, both in virgin and aged samples. In addition, PAHs are more concentrated in the neutral fraction, while N-PACs and O-PAHs are more in the acidic and basic acidic and asphaltenes. With the aging process, N- PACs (e.g. nitroanthracene and nitropyrene) and O-PAHs (e.g. phenanthrenecarboxyaldehyde and hydroxypyrene) are the most affected, mainly in the acidic fraction, and can be considered markers of this process. In relation to the Ni and V compounds, both decrease with the aging process, Ni having a loss between 45 and 50% and V between 35 and 40% both in the acid fractions of AC. The results presented here are important in the sense of understanding a little more on the phenomena involved in the aging process of AC and of the contributions that these compounds have in chemical modifications. Based on this fact, possible chemical and physical transformations were proposed based on the study of 6 different asphalt binders and the predicted reactions in the literature for AC (oxidation, condensation and volatilization). A total of 7 PAHs were indicated as the most reactive in the binders and 4 porphyrins of Ni and V were studied as models of organic compounds involved in aging under the action of UV radiation.